Cosmetic ethnobotany practiced by tribal women of Kashmir Himalayas - Hamayun Shaheen; Jaweria Nazir; Syeda Sadiqa Firdous; Abd- (Mashhad University of Medical Sciences, 2014)
Objective: Himalayan mountain populations have been dependent upon indigenous plant resources for their health care for many years. Tribal women are interested in use of local herbs for cosmetic purposes. The present work is based on the results of research conducted on cosmetic uses of some important plants by the tribal women in District Poonch, Azad Kashmir Pakistan. Materials and Methods: An ethno botanical survey was carried out during summer 2012. The data were collected from 310 female informants from 16 villages using questionnaire method and semi structured interviews. Results: A total of 39 plants species belonging to 20 families, being used for various cosmetic purposes were recorded. Indigenous species are traditionally used by the locals for problems including acne (16%), hair growth (11%), bad breath (12%), facial spots (9%), allergy, (9%), fairness (8%), wrinkles (8%), eye and lip care (9%). Seventy different recipes were recorded to be practiced by locals using herbal parts. The major plant parts utilized in herbal recipes included fruit (32.8%), Leaves (25.2%), seeds (13.4%) and roots (8.9%). Women of older (>30 years) age group showed greater (67%) response regarding knowledge and practice of cosmetic herbs. Conclusion: This study was the 1st ever project focusing on cosmetic perspectives of ethno-botany in the area. Our study contributes to an improved understanding of ignored aspect of cosmetic ethnobotany among the local women. Further detailed investigations are recommended to record and preserve precious ethno-botanical knowledge of the area.